Extraordinary pseudocapacitive energy storage triggered by phase transformation in hierarchical vanadium oxides - Bo-Tian Liu (Nature Portfolio, 2018)
Pseudocapacitive materials could enable high-performance electrochemical supercapacitors, but their practical capacitance and power density remain low. Here the authors show that in situ phase transformation triggers extraordinary pseudocapacitive energy storage in metallic isomeric vanadium oxides.